Comparison of phase composition, morphology and electrochemical property for Li3−xNaxV2(PO4)3 (x=0.5, 1.5 and 2.0) as lithium storage cathode materials. (10th August 2015) - Mao, Jinli; Shao, Lianyi; Li, Peng; Lin, Xiaoting; Shui, Miao; Long, Nengbing; Shu, Jie
Graphical abstract: Highlights: Li3−x Nax V2 (PO4 )3 is prepared by a solid-state reaction method. Li2.5 Na0.5 V2 (PO4 )3 is a three-phase mixture. Both Li1.5 Na1.5 V2 (PO4 )3 and LiNa2 V2 (PO4 )3 are two-phase composite. Lithium ion diffusion coefficient is detected by cyclic voltammetry. Structural change of LiNa2 V2 (PO4 )3 is observed by in-situ XRD. Abstract: Three Li3-x Nax V2 (PO4 )3 (x=0.5, 1.5 and 2.0) samples are synthesized by a traditional solid-state reaction method in this work. Their phase composition, surface morphology and electrochemical property are described and compared by using various physical/chemical methods. Phase analysis results reveal that Li2.5 Na0.5 V2 (PO4 )3 consists of monoclinic Li3 V2 (PO4 )3, rhombohedral Li3 V2 (PO4 )3 and rhombohedral Na3 V2 (PO4 )3. While, both Li1.5 Na1.5 V2 (PO4 )3 and LiNa2 V2 (PO4 )3 are the two-phase mixture consisted of rhombohedral Li3 V2 (PO4 )3 and rhombohedral Na3 V2 (PO4 )3 . Electrochemical testing results reveal that LiNa2 V2 (PO4 )3 and Li1.5 Na1.5 V2 (PO4 )3 can deliver the initial discharge capacities of 101.4 mAh g −1 and 108.6 mAh g −1 with a long potential plateau at 3.69 V, respectively. In contrast, Li2.5 Na0.5 V2 (PO4 )3 presents an initial discharge capacity of 111.7 mAh g −1 with four potential plateaus. High lithium ion diffusion coefficient in Li2.5 Na0.5 V2 (PO4 )3 indicates that the existence of monoclinic Li3 V2 (PO4 )3 phase can improve the ionic conductivity and then be responsible for good electrochemical performance. Besides, in-situ X-ray diffraction observation of LiNa2 V2 (PO4 )3 demonstrates that the phase transition is not fully reversible but quasi-reversible during the lithiation-delithiation process. The partial irreversibility of structural evolution for LiNa2 V2 (PO4 )3 induces the capacity loss upon repeated cycles.